Jennifer made an error when converting y=x²+2x+7, to vertex form. In which step did she make the error? Explain your answer and provide the correct form of the equation in vertex form.
A. y=x²+2x+7
B. y=(x²+2x)+7
C. y=(x²+2x+1)+7
D. y=(x+1)² +7
(Will mark brainliest)

Respuesta :

Answer:

D

Step-by-step explanation:

To convert a quadratic from y = ax2 + bx + c form to vertex form, y = a(x - h)2+ k, you use the process of completing the square. Let's see an example. Convert y = 2x2 - 4x + 5 into vertex form, and state the vertex.

Answer: Below.

Step-by-step explanation:

Vertex Form: [tex]y=a(x-h)^2+k[/tex]

[tex]y=x^2+2x+7\\y=(x^2+2x)+7\\y=(x^2+2x+1)-1+7\\y=(x+1)^2+6[/tex]

Find the number that make the terms able to complete the square and when you get that number (the number is 1 because we need to complete the square.) then you add -1 outside of the bracket as you get -1+7 = 6

The vertex is (-1,6)

So the vertex form is actually [tex]y=(x+1)^2+6[/tex] and not +7.

(If you don't believe, use any apps to draw the graph and it'll give the vertex at (-1,6)